Physical-Chemical Treatment of Water and Wastewater - Sincero, Arcadio P (CRC Press, 2009)
The books currently available on this subject contain some elements of physical-chemical treatment of water and wastewater but fall short of giving comprehensive and authoritative coverage. They contain some equations that are not substantiated, offering empirical data based on assumptions that are therefore difficult to comprehend. This text brings together the information previously scattered in several books and adds the knowledge from the author's lectures on wastewater engineering.